Environmental Accounting Disclosure in ASEAN Countries - Haqi Fadilah; Syahril Djajang (STIE Perbanas Surabaya, 2017)
This study aims to determine whether there is a difference between the scores of country-based environmental accounting disclosure (in the ASEAN region) and industrybased environmental accounting disclosure (in real estate, forest/agriculture, consumer goods, hospitals, energy, and chemicals/pharmaceuticals). The research method used is One-Way ANOVA difference test. The results show that there is a difference in the scores of country-based environmental accounting disclosure. The difference is between Indonesia and Singapore and between Indonesia and the Philippines. Furthermore, there is no significant difference in the scores of industry-based environmental accounting disclosure, as well as when viewed from each of ASEAN countries. Each country needs to have more stringent regulations and policies to require each company to present the environmental accounting disclosure in the annual report or sustainability report as a form of corporate legitimacy to the public. In addition, there should be a revision of the nature of the environmental accounting disclosure in the financial accounting standards, from voluntary to mandatory. It is intended that every company of various types of industries really pay attention to the environmental impact problems arising from its operational activities.